How do you multiply (9k+q)(2k-q)(9k+q)(2kq)?

3 Answers
Mar 29, 2018

18k^2 - 7kq - q^218k27kqq2

Explanation:

To multiply two polynomials, simply multiply each term in the first parenthesis with each term in the second, and sum everything.
So, we have:

  • First element of first parenthesis times first element of second parenthesis: 9k * 2k = 18k^29k2k=18k2
  • Second element of first parenthesis times first element of second parenthesis: q * 2k = 2kqq2k=2kq
  • First element of first parenthesis times second element of second parenthesis: 9k * -q = -9kq9kq=9kq
  • Second element of first parenthesis times second element of second parenthesis: q * (-q) = -q^2q(q)=q2

Summing it up:

18k^2 + 2kq - 9kq - q^2 = 18k^2 - 7kq - q^218k2+2kq9kqq2=18k27kqq2

Mar 29, 2018

Use FOIL methos (First,Outer,Inner,Last)

Explanation:

(9k+q)(2k-q)
(9k2k) + (9k-q2k) + (q-q)
=18k^218k2-9kq+2kq- q^2q2

Hope this helps!

Mar 29, 2018

18k^2-q^2-7kq18k2q27kq

Explanation:

(9k+q)(2k-q)
=)18k^2-q^2+2kq-9kq18k2q2+2kq9kq
=)18k^2-q^2-7kq18k2q27kq